2D Kinetic Analysis of TCR and CD8 Coreceptor for LCMV GP33 Epitopes - Kolawole, Elizabeth M.; Andargachew, Rakieb; Liu, Baoyu; Jacobs, Jesica R.; Evavold, Brian D. (Frontiers in Immunology, 2018)
The LCMV GP33 CD8 epitope has long been one of the most widely used antigens in viral immunology. Of note, almost all of the in vitro analyses of CD8 T cell responses to this epitope make use of an altered peptide ligand (APL) in which the cysteine from the original 9-mer peptide (KAVYNFATC) is substituted by a methionine at position 41 (KAVYNFATM). In addition, it is possible that the antigen processed during natural LCMV infection is an 11-mer peptide (KAVYNFATCGI) rather than the widely used 9-mer. Although previous affinity measurements using purified proteins for these antigen variants revealed minimal differences, we applied highly sensitive two dimensional (2D) biophysical based techniques to further dissect TCR interaction with these closely related GP33 variants. The kinetic analyses of affinity provided by the 2D micropipette adhesion frequency assay (2D-MP) and bond lifetime under force analyzed using a biomembrane force probe (BFP) revealed significant differences between 41M, 41C and the 11-mer 41CGI antigen. We found a hierarchy in 2D affinity as 41M peptide displayed augmented TCR 2D affinity compared to 41C and 41CGI. These differences were also maintained in the presence of CD8 coreceptor and when analysis of total TCR:pMHC and CD8:pMHC bonds were considered. Moreover, the three ligands displayed dramatic differences in the bond lifetimes generated under force, in particular the 41CGI variant with the lowest 2D affinity demonstrated a 15-fold synergistic contribution of the CD8 coreceptor to overall bond lifetime. Our analyses emphasize the sensitivity of single cell and single bond 2D kinetic measurements in distinguishing between related agonist peptides.